Reprogramming of the ERRα and ERα target gene landscape triggers tamoxifen resistance in breast cancer - Thewes, Verena; Benes, Vladimir; Burwinkel, Barbara; Sinn, Peter; Schneeweiss, Andreas (Cancer research, 2015)
Endocrine treatment regimens for breast cancer that target the estrogen receptor-α (ERα) are effective, but acquired resistance remains a limiting drawback. One mechanism of acquired resistance that has been hypothesized is functional substitution of the orphan receptor estrogen-related receptor-α (ERRα) for ERα. To examine this hypothesis, we analyzed ERRα and ERα in recurrent tamoxifen-resistant breast tumors and conducted a genome-wide target gene profiling analysis of MCF-7 breast cancer cell populations that were sensitive or resistant to tamoxifen treatment. This analysis uncovered a global redirection in the target genes controlled by ERα, ERRα, and their coactivator AIB1, defining a novel set of target genes in tamoxifen-resistant cells. Beyond differences in the ERα and ERRα target gene repertoires, both factors were engaged in similar pathobiologic processes relevant to acquired resistance. Functional analyses confirmed a requirement for ERRα in tamoxifen- and fulvestrant-resistant MCF-7 cells, with pharmacologic inhibition of ERRα sufficient to partly restore sensitivity to antiestrogens. In clinical specimens (n = 1041), increased expression of ERRα was associated with enhanced proliferation and aggressive disease parameters, including increased levels of p53 in ERα-positive cases. In addition, increased ERRα expression was linked to reduced overall survival in independent tamoxifen-treated patient cohorts. Taken together, our results suggest that ERα and ERRα cooperate to promote endocrine resistance, and they provide a rationale for the exploration of ERRα as a candidate drug target to treat endocrine-resistant breast cancer. Cancer Res; 75(4); 720-31. ©2015 AACR.